2013
DOI: 10.2807/1560-7917.es2013.18.30.20544
|View full text |Cite
|
Sign up to set email alerts
|

Imported leishmaniasis in the Netherlands from 2005 to 2012: epidemiology, diagnostic techniques and sequence-based species typing from 195 patients

Abstract: Leishmaniasis is an imported disease in the Netherlands. We report data for the period between 2005 and 2012, on clinical presentation, country where leishmaniasis was acquired, and causative species, for 195 civilian and military patients who had travelled abroad. Most patients were affected by cutaneous leishmaniasis (CL) (n=185 patients), while visceral leishmaniasis (VL) (n=8 patients) and mucocutaneous leishmaniasis (n=2 patients) were less frequently observed. All VL patients had been infected in Europe.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
44
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 28 publications
(48 reference statements)
6
44
0
Order By: Relevance
“…This is in agreement with the recognized value of rK39 as a good serological marker for leishmaniosis (Porrozzi et al 2007). Still, regional differences in antigen performance have been already reported, the performance of rK39 (for the human visceral leishmaniasis) is known to be diminished in subSaharan Africa (Pattabhi et al 2010;Bezuneh et al 2014;Mukhtar et al 2015). Subtle genetic differences in Leishmania strains are sufficient to influence the performance of the recombinant antigens (Abass et al 2015).…”
Section: Discussionsupporting
confidence: 87%
“…This is in agreement with the recognized value of rK39 as a good serological marker for leishmaniosis (Porrozzi et al 2007). Still, regional differences in antigen performance have been already reported, the performance of rK39 (for the human visceral leishmaniasis) is known to be diminished in subSaharan Africa (Pattabhi et al 2010;Bezuneh et al 2014;Mukhtar et al 2015). Subtle genetic differences in Leishmania strains are sufficient to influence the performance of the recombinant antigens (Abass et al 2015).…”
Section: Discussionsupporting
confidence: 87%
“…Similar epidemiological evidence showed that in the Netherlands the number of CL cases doubled between 1990 and 2000, with Europe, Africa, Asia, and the New World (Latin America) as the most common sources of infection [71]. More recent data showed an increase in Netherlands patients diagnosed with CL between 2005 and 2012 compared to the periods from 1979 to 1988 and 1990 to 2000 [61]. CL in Guyana (an overseas region of France) is the major source of exotic cases imported to mainland France [41].…”
Section: Cutaneous Leishmaniasismentioning
confidence: 48%
“…As the important question regarding the possibility that any of these vertebrate species can serve as reservoirs and participate in the establishment and spread of the parasite in new foci is still unanswered (Maia and Campino, 2011;Antoniou et al, 2013), cats and red foxes need to be at least considered as a potential threat and surveys should be performed to investigate the capacity of these animal species to harbour L. infantum (Mencke, 2011). From a public health point of view, human medicine professionals should include leishmanioses (VL and CL) in the differential diagnosis in suspected patients returning from southern Europe (Ehehalt et al, 2014) and an increased awareness amongst clinicians about these parasitoses, availability of reliable diagnostic tests and specific treatment guidelines in non-endemic countries is also a must (Bart et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Bogdan et al (2001) reported VL in a 15-month-old boy that had never been outside of Germany. In the Netherlands, for the period between 2005 and 2012, leishmaniosis was diagnosed in 195 civilian and military patients who had travelled abroad (Bart et al, 2013). Most patients were affected by CL (n = 185), while VL (n = 8) and mucocutaneous leishmaniosis (n = 2) were less frequently observed.…”
Section: Humans and Other Hosts Of L Infantum In Europementioning
confidence: 99%
See 1 more Smart Citation